Mechanism study of advanced lightning strike protection composite systems using a miniature tip discharge system. (April 2023) - Bai, Yunxiang; Zhu, Mingquan; Wang, Shijun; Gao, Feng; Gao, Runyi; Qu, Yusong; Cui, Xuwei; Wang, Guorui; Liu, Luqi; Zhang, Hui; Zhang, Zhong
Abstract: Carbon nanotubes show great potential in lightning strike protection (LSP) of carbon fiber reinforced plastic (CFRP) instead of metallic meshes/foils. However, the LSP mechanism is unclear, which limits their further refinement and applications. The general simulated lightning strike tests in previous reports are usually complex and expensive. The variation in test conditions can lead to the direct comparison of the obtained conclusions being virtually invalid. Herein we design a miniature tip discharge system (MTDS) to simulate the lightning strike environment in the laboratory and study the failure mechanism of CNT film-based advanced LSP composite systems. The main failure mechanism of the CNT film for LSP is thermal ablation, and the parameters affecting LSP testing results include the electrical conductivity, specific heat capacity, film size, electrode tip diameter, electrical stress rates, etc. The introduced isolation layer also contributes to the LSP effect, mainly by electrical insulation, thermal resistance, and thermal insulation.